Data Center Data Warehouse Development at Z Bali Clinic Using the Kimball Nine-Step Method - Wira Partha, I Gusti Ngurah; Mamang Weking, Philipus Novenando; Arya Mertasana, Putu (International Journal of Engineering and Emerging Technology, 2019)
Z Bali Clinic has implemented a clinical information system as an operational system. However, the system applied is only limited to carrying out registration and payment functions. Over time, the number of patients from the Z Bali Clinic is increasing and causes more and more complex patient visit data to be managed. The data is managed to be used in making reports. However, the process of making the report is still done through manual calculations, causing it to become an obstacle in the data processing and reporting process. In this study, the process of developing a Data center data warehouse at Z Bali Clinic Using the Kimball Nine-Step Method, where the data warehouse can be used as a center for processing and analyzing outpatient visit data, and to produce reports that can facilitate the executive in analyzing data on outpatient visits as consideration in making decisions at the Z Bali Clinic.